حقوق ِانسانی کامذہبی تصور: Religious Paradigm of Human Rights - Sofia Mehboob; Dr. Mustafeez Alvi (MEI, 2023)
Human rights in the modern world are considered to be the basic rights of a man based on being a human being. These rights belong to every person in the world and remain consistent with him/her from birth until death. These rights are basic, universal and un-alienable. The history of human rights starts since early human civilizations; evolved in the modern form since the Western renaissance. The religion as a worldview and as a code of human life, always have an important role in human life and society. It has its concept of rights and responsibilities but never thought of in the modern socio-political terms. The Prophet PBUH) of Islam established the very basics of rights and responsibilities of an individual to be a responsible citizen. Therefore, the study of religions, clearly states that human rights are the name of the basic principles, which maintain human relationships in society. The following study analyses the same idea in brief.